MEDIA MASSA SEBAGAI AGEN SOSIALISASI IDEOLOGI - Chakim, Sulkhan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
This passage discusses the fact that any media in this world is never separated frompolitical and ideological interests. Various types of domination and subordination are alwayscontinuously created and reproduced for the existence and sustainability of certain individualsor groups.Legitimacy in the capital system is very crucial in to support its role as a source ofpower. Three kinds of important capital are economic, politic, and cultural capital. Thesekinds of capital are the source of power and cause some social inequalities. Capitalism spreadsout in all sides of human life, is produced and sustained continuously through various socialagents.